On the factors of choosing the country of legal transplant’s origin - Kovalyshyn, Oleksandr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
Reform of the national and international financial architecture, along with economic and political (democratic) development, is the paramount target of emerging economies and developing countries worldwide. Moreover, it is an ongoing process in regional or inter- national economic integration arrangement.Diffusion of law has been an important topic in comparative law at least since the publication of Alan Watson’s seminal book on “Legal Transplants” in 1974. The very existence of legal families spanning the globe is due to the diffusion of legal models during colonial times.The “legal transplant” metaphor has been successful in conveying a wide-spread perception of law as quasi-organic matter, as well as a general idea about the complex and sensitive nature of any attempt to make laws and legal institutions that have evolved in one particular legal and institutional environment, work outside their natural “habitat”. The author emphasizes that legal transplants play an important role in commercial law, especially  taking into account the globalization processes that occur in the world. The article is devoted to the identification of those factors that determine the use of a particular legal system when choosing legal transplants. Factors that determine the leading role of US law in the dissemination of their specific legal  institutions or legal norms, especially in the field of commercial  law, are analyzed. The author systematizes the factors that have a decisive influence when choosing a particular legal transplant.